The best Australian essays 2016 - Williamson, Geordie (Carlton, Victoria : Black Inc., 2016)
Agile hard-hitting, symphonic Australia has much to celebrate in its non-fiction writing. Geordie Williamson gathers the Best Australian Essays in his role as editor for a second year. Expect an enthralling mix of evocation and ideas, politics and culture.
Includes bibliographical references (pages 327-329)
Also available online.
Keywords: Speeches, addresses, etc., Australian; Australian essays -- 21st century -- Collections; Speeches, addresses, etc., Australian -- 21st century; Australian essays -- 21st century; Australian